IMPACT OF EU’S SINGLE EUROPEAN MARKET ON E-BOOKS AND ITS IMPLICATIONS REGARDING PUBLISHING INDUSTRIES IN SMALL COUNTRIES - TOMAŠEVIĆ, NIVES; DESPOT, IVONA (Knygotyra, 2014)
Most European e-book markets are currently being created. Publishers are going through a transitional phase and together with the printed content creators becoming the designers of e-content. The integration of technology into business processes is becoming an important business challenge together with the creation of new publishing products. All this is possible only through mutual work of other sectors in the creative industries. The paper tries to show the possibilities a small publisher has and identify the obstacles to the development of such markets. It discusses the advantages of a traditional publisher compared to new entrants, the skills that a traditional publisher develops and implements. One of the obstacles for the development of a small market is a high VAT rate for e-books throughout Europe. A special emphasis will be put on the Croatian market, which upon the entrance to the European Union had to apply a new tax policy regarding books. KEYWORDS: e-book, electronic publishing, VAT/GST/Sales Tax Rate, Single European digital market, small market, innovative publishing products, Croatia.